Disaster Early Warning and Information Services Meteorology, Climatology and Geophysics Agency’s Employees Performance Observed from their Motivation and Competency - Deffi Ayu Puspito Sari; Malahayati Malahayati; Tirton Nefianto; IDK Kertawidana (International Journal of Multi Discipline Science, 2018)
Improvement is needed in the early warning system and information services of Indonesia Agency for Meteorology, Climatology and Geophysics (Badan Meteorologi, Klimatologi dan Geofisika-BMKG) in term of speed, and accessibility by rural communities. This paper analyzes the factors related to the motivation and competency of BMKG employees’ performance in giving information services related to early warning system. The aim is to determine the effect of motivation and competency partially and simultaneously toward BMKG’s employees performance. Using quantitative method with proportionate stratified random sampling technique, total 80 respondents were interviewed among 389 population of BMKG’s employees who work on Deputy of Meteorology, Climatology, and Geophysics. The result indicated that the motivation and competency have significant impact to the BMKG’s employees performance. R2 is 0.832 which means that the motivation and competency simultaneously have significant impact to employees performance about 83.2% while the remaining 16.8% influenced by others variable outside the variables studied. The data analyzed using double linear regression in SPSS version 24,  the equation regression obtained is: Y= 9,429 + 0,408X1 + 0,822X2, indicating that effect of motivation factor is lower than competency factor toward employees performance. Therefore BMKG Head Office needs to improve the competency of employees more than motivate them in order to improve its performance on information services and disaster early warning.